PENGAMBILAN KEPUTUSAN UNTUK KUALITAS AIR PADA TAMBAK UDANG MENGGUNAKAN FUZZY LOGIC CONTROL - Dwisaputra, Indra; Rolastin, Boy; Irwan, Irwan; Sateria, Angga (Gema Teknologi, 2019)
Indra Dwisaputra, Boy Rolastin, Irwan, Angga Satera, in this paper explain that one commodity that can be used as a superior post-mining area such as Bangka Belitung is shrimp ponds. Touch of technology is needed because of high rainfall in this area so that changes in temperature, humidity, salinity and pH are more dynamic. Then we need a control to determine the water quality in shrimp ponds to avoid crop failure. This research was conducted by means of simulations to make it easier to analyze the results before applying. Fuzzy logic control (FLC) method is used for the water quality decision making system. By utilizing 3 input variables such as temperature, salinity and pH of water and output is an index of water quality from a scale of 0-100. The Mamdani method is applied to FLC with 27 fuzzy rules. The simulation results show that a change in one of the input variables can cause water quality to drop to 70. When there are changes in the two input variables, it can reduce water quality by 25.1. FLC can work well in decision making for water quality in shrimp culture.